HUBUNGAN PRESTASI PRAKEIN SISWA DAN MINAT BERWIRAUSAHA SISWA TKR SMK MUHAMMADIYAH 1 SLEMAN - Anggit Wahyu Nugroho; Sudiyanto Sudiyanto (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aimed to find out the relationship between internship achievement and entrepreneurial interest among students of light vehicle engineering (LVE) of SMK Muhammadiyah 1 Sleman. This was a correlational study. The research subjects were 70 LVE students at SMK Muhammadiyah 1 Sleman with a total of 70 students. The data were collected using questionnaires and documents. The data were analyzed using product moment statistics. The results of the study showed that the students’ industrial internship achievement was 56% in the good category, their entrepreneurial interest was 53% in the high category, and there was a relationship between the internship achievement and the entrepreneurial interest  among the students of LVE of SMK Muhammadiyah 1 Sleman in the 2018/2019 academic year. The relationship between industrial internship achievement and entrepreneurial interest was classified as a moderate correlation with a Pearson Correlation coefficient of 0.599. The outstanding values were knowledge and expectation of working through entrepreneurship. Meanwhile the weak values were attitude towards and attention to entrepreneurship activities.